TO THE QUESTION OF THE EFFECTIVENESS OF SOCIO-CULTURAL ADAPTATION OF CHILDREN WITH SPECIAL NEEDS - Mirzajonova Eleonora Topvoldievna (Journals Park Publishing, 2022)
This article describes the problems of children’s socialization in family and out of the family. The article is dedicated to the problem of the socialization of children, with special needs in the family and outside the family through the organization of various form of sociocultural activities and effective adaptive practices, creating conditions for formation and development of their active life position.
Keywords: children with special needs; sociocultural competence,; sociocultural activities